2021
DOI: 10.1109/access.2021.3063676
|View full text |Cite
|
Sign up to set email alerts
|

An Automated Sensor Fusion Approach for the RUL Prediction of Electromagnetic Pumps

Abstract: The remaining useful life (RUL) prediction of industrial cyber-physical system components demands the use of reliable prognostics parameters and frameworks. Against the traditional use of a single measure of degradation, data from multiple sensors provide abundant characteristic information for modeling, assessing, and extracting useful parameters via appropriate signal processing and sensor fusion methods. This study introduces a multi-sensor prognostics approach which merges highly prognosible statistical fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 36 publications
0
18
0
Order By: Relevance
“…Ongoing research on reliability studies suggests that hydraulic components are some of the most complex systems to accurately monitor and has motivated diverse prognostic and health management (PHM) methodologies for these components-pumps, valves, actuators, etc. This complexity is a result of the thermodynamic, fluid dynamic, mechanical, and electrical processes (not to mention uncertainties) which simultaneously occur as the components are in operation [13]; nonetheless, vibration monitoring, acoustic emission monitoring, and pressure monitoring are among the most popular methods for pumps [4,14].…”
Section: Related Workmentioning
confidence: 99%
See 4 more Smart Citations
“…Ongoing research on reliability studies suggests that hydraulic components are some of the most complex systems to accurately monitor and has motivated diverse prognostic and health management (PHM) methodologies for these components-pumps, valves, actuators, etc. This complexity is a result of the thermodynamic, fluid dynamic, mechanical, and electrical processes (not to mention uncertainties) which simultaneously occur as the components are in operation [13]; nonetheless, vibration monitoring, acoustic emission monitoring, and pressure monitoring are among the most popular methods for pumps [4,14].…”
Section: Related Workmentioning
confidence: 99%
“…In previous studies on failure diagnostics of electromagnetic pumps [4,27,28], filter clogging has shown to be one of the high-ranking failure modes. In this study, a natural running condition (powered by 220 V, 60 Hz) was simulated for a VSC63A5 solenoid Pump whereby the working fluid-5 Litres of diesel was contaminated with ten(10) grams of Iron(III) oxide (Fe 2 O 3 ).…”
Section: Testbed Description and Data Acquisitionmentioning
confidence: 99%
See 3 more Smart Citations